Molecular Diagnosis as an Alternative for Public Health Surveillance of Leptospirosis in Colombia - Margarita Arboleda; Mariana Mejía-Torres; Maritza Posada; Nicaela Restrepo; Paola Ríos-Tapias; Luis Alberto Rivera-Pedroza; David Calle; Miryan M. Sánchez-Jiménez; Katerine Marín; Piedad Agudelo-Flórez (Microorganisms, 2023)
Leptospirosis represents a public health problem in Colombia. However, the underreporting of the disease is an unfortunate reality, with a clear trend towards a decrease in cases since 2019, when the guidelines for its confirmatory diagnosis changed with the requirement of two paired samples. The purpose of this review is to highlight the importance of leptospirosis. While the access to rapid diagnosis is available at practically all levels of care for dengue and malaria, leptospirosis—a doubly neglected disease—deserves recognition as a serious public health problem in Colombia. In this manner, it is proposed that molecular tests are a viable diagnostic alternative that can improve the targeted treatment of the patient and the timeliness of data and case reporting to SIVIGILA, and reduce the underreporting of the disease. Taking advantage of the strengthened technological infrastructure derived from the SARS-CoV-2 pandemic for molecular diagnosis in Colombia, with a network of 227 laboratories distributed throughout the national territory, with an installed capacity for PCR testing, it is proposed that molecular diagnosis can be used as an alternative for early diagnosis. This would allow case confirmation through the public health network in Colombia, and, together with the microagglutination (MAT) technique, the epidemiological surveillance of this disease in this country would be strengthened.